2003
DOI: 10.1111/j.1752-1688.2003.tb04429.x
|View full text |Cite
|
Sign up to set email alerts
|

EFFECTS OF CLIMATE VARIABILITY ON RIVERS: CONSEQUENCES FOR LONG TERM WATER QUALITY ANALYSIS1

Abstract: Associations between the El Nino Southern Oscillation (ENSO) climate pattern and temporal variability in flow and 12 water quality variables were assessed at 77 river sites throughout New Zealand over a 13‐year period (1989 through 2001). Trends in water quality were determined for the same period. All 13 variables showed statistically significant linear regression relationships with values of the Southern Oscillation Index (SOI). The strongest relationships were for water temperature (mean R2= 0.20), dissolve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
39
0
1

Year Published

2004
2004
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(42 citation statements)
references
References 29 publications
2
39
0
1
Order By: Relevance
“…Positive values (La Niña) are generally characterised by increased moist, rainy conditions to the north-east of the North Island, and reduced rainfall to the south and south-west of the South Island (Kidson and Renwick 2002). Trends in New Zealand water quality were correlated with SOI values over a 13-year period, with statistically significant linear regression relationships being found for 13 variables (Scarsbrook et al 2003). The strongest relationships were for water temperature (mean R 2 ¼ 0.20), FRP (0.18), and NO X -N (0.17).…”
Section: Long-term Monitoringmentioning
confidence: 77%
See 1 more Smart Citation
“…Positive values (La Niña) are generally characterised by increased moist, rainy conditions to the north-east of the North Island, and reduced rainfall to the south and south-west of the South Island (Kidson and Renwick 2002). Trends in New Zealand water quality were correlated with SOI values over a 13-year period, with statistically significant linear regression relationships being found for 13 variables (Scarsbrook et al 2003). The strongest relationships were for water temperature (mean R 2 ¼ 0.20), FRP (0.18), and NO X -N (0.17).…”
Section: Long-term Monitoringmentioning
confidence: 77%
“…The strongest relationships were for water temperature (mean R 2 ¼ 0.20), FRP (0.18), and NO X -N (0.17). The analysis indicated that effects on water quality were not necessarily a direct consequence of changes in flow associated with rainfall variation, and that changes in management were not directly responsible (Scarsbrook et al 2003). The authors suggest that water quality trends in New Zealand should take climatic influences into account when ascribing causes for trends, which implies that monitoring records should be long enough to discriminate land-management consequences from those induced by 3-7 year climate cycles.…”
Section: Long-term Monitoringmentioning
confidence: 99%
“…As with any monitoring program, the value of sustained high-quality measurements only increases with time, and the New Zealand example allows insights into biological, physical and chemical linkages and changes, which would not be obtainable otherwise (e.g. Scarsbrook et al 2000Scarsbrook et al , 2003.…”
Section: Improved Monitoring For Australia's Aquatic Environmentsmentioning
confidence: 99%
“…Results from the available long-term hydroecological studies indicate that instream communities are influenced by variations in both the climatological (Bradley and Ormerod, 2001;Daufresne et al, 2003;Scarsbrook et al, 2003) and hydrological regimes (e.g., Lamouroux et al, 2006;Monk et al, 2006, Scarsbrook, 2002Wagner and Schmidt, 2004;Wood et al, 2001). However, attempts to quantify macroinvertebrate community response to river flow variability, and in particular high and low flows, are currently limited in terms of their temporal (typically <5 years study period) and/or geographical coverage (e.g., Caruso 2002;Clausen and Biggs, 1997;Sheldon and Thoms, 2006;Suren and Jowett, 2006).…”
Section: Introductionmentioning
confidence: 99%